Nurturing holistic grads - Kulasagaran, Priya (Sunday Star, 2013)
A conference held jointly by a public and private university to both enlighten and provoke discussion saw several renowned speakers of different backgrounds, speaking on topics that ranged from students affairs, political literacy, social skills and volunteerism, among others.